Dynamic changes in mourse sperm midpiece during acrosomal exocytosis - Jabloñski, Martina (2021)
As the mammalian sperm are ejaculated from the male reproductive tract, they are not capable of fertilizing oocytes. In order to gain fertilization competence, they must undergo a series of biochemical and physiological events as they travel across the female tract that are collectively known as capacitation. One of the outcomes of capacitation is the ability to undergo acrosomal exocytosis, a unique secretory event. It occurs as the result of fusion events between the plasma membrane and a specialized vesicle called acrosome.